365 fakta jenaka untuk anak-anak Bernadette Mc Carver Snyder ; diterjemahkan oleh M. I. Kusumastuty & Dwi Koratno - SNYDER, Bernadette Mc Carver; Dwi Koratno; Kusumastuty, M. I (2001)
121 hlm ilus 23x20 cm